2014
DOI: 10.1159/000357824
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms in the Pathogenesis of Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR), which arises as a result of an increasing incidence of diabetes mellitus, has gradually become a common disease. Due to its complex pathogenesis, the treatment means of DR are very limited. The findings of several studies have shown that instituting tight glycemic control in diabetic patients does not immediately benefit the progression of retinopathy, and the benefits of good control persist beyond the period of good glycemic control. This has led to the concept of persistent epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 97 publications
1
15
0
Order By: Relevance
“…Studies have shown that DR may be due to persistent epigenetic modifications because the improvement of diabetes mellitus does not imply beneficial effects on DR even in the long term. This is corroborated by other evidence that has linked epigenetic modifications to complications of diabetes [166].…”
Section: Epigenetic Effects Of Agessupporting
confidence: 82%
“…Studies have shown that DR may be due to persistent epigenetic modifications because the improvement of diabetes mellitus does not imply beneficial effects on DR even in the long term. This is corroborated by other evidence that has linked epigenetic modifications to complications of diabetes [166].…”
Section: Epigenetic Effects Of Agessupporting
confidence: 82%
“…Diabetic retinopathy (DR) is a neurovascular degenerative disease caused by multifactorial and complex mechanisms (Zeng & Chen ; Pusparajah et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…This complication is expected to increase in the coming decades because of its limited treatment options, complex pathogenesis and lack of safe delivery systems to target the retina. 30,31 DR is a common microvascular dysfunction which is characterized by cellular capillary formation, inner blood-retinalbarrier breakdown, endothelial dysfunction, pericyte loss, thickening of the capillary basement membrane and microaneurisms (non-proliferative diabetic retinopathy). Finally, it will lead to the formation of leaky blood vessels and new fragile and end up with proliferative diabetic retinopathy and blindness.…”
Section: Diabetic Retinopathymentioning
confidence: 99%